2013
DOI: 10.1186/1748-5908-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Preventive evidence into practice (PEP) study: implementation of guidelines to prevent primary vascular disease in general practice protocol for a cluster randomised controlled trial

Abstract: BackgroundThere are significant gaps in the implementation and uptake of evidence-based guideline recommendations for cardiovascular disease (CVD) and diabetes in Australian general practice. This study protocol describes the methodology for a cluster randomised trial to evaluate the effectiveness of a model that aims to improve the implementation of these guidelines in Australian general practice developed by a collaboration between researchers, non-government organisations, and the profession.MethodsWe hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…At the time of writing the questionnaire, the TDF had only been applied in two quantitative studies [ 40 , 41 ] and demonstrated varying degrees of internal consistency in domains and either one [ 41 ] (propensity to act) or three [ 40 ] (capability, opportunity, motivation) factor explanatory models. Subsequent quantitative applications [ 22 , 52 , 53 ] have shown good discriminant validity, collated a wider array of domain items, and demonstrated levels of internal consistency similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…At the time of writing the questionnaire, the TDF had only been applied in two quantitative studies [ 40 , 41 ] and demonstrated varying degrees of internal consistency in domains and either one [ 41 ] (propensity to act) or three [ 40 ] (capability, opportunity, motivation) factor explanatory models. Subsequent quantitative applications [ 22 , 52 , 53 ] have shown good discriminant validity, collated a wider array of domain items, and demonstrated levels of internal consistency similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Data collection methods will extend over 12 months and the commonly accepted term for “active” patients will be adopted to maintain consistency within the data [ 30 ]. Paper-based surveys of practitioners will test GP and PN self-reported knowledge and self-efficacy (adapted from another preventive health study [ 33 ]) and health care utilisation following HKC will be captured (from government Medicare insurance services) to obtain important data regarding health outcomes. Arising from the pilot study was a recommendation to develop a web based module to streamline delivery of components of the training.…”
Section: Discussionmentioning
confidence: 99%
“…Assisting patients to attain the desired goals of diabetes selfmanagement is difficult, and failures frequently occur [29]. Intensive interventions have shown greater potential for positive results [30][31][32] and larger scale randomized trials designed to identify intervention strategies to control T2DM are currently underway [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%